Experience-dependent structural plasticity targets dynamic filopodia in regulating dendrite maturation and synaptogenesis - Chengyu Sheng (Nature Portfolio, 2018)
During development, dendrites display structural plasticity, as reflected in the appearance of long, thin and highly motile dendritic filopodia. Here, the authors examine dendritic dynamics of ventral lateral neurons in the developing Drosophila larva, and identify Amphiphysin as an important regulator of this process.